PENGARUH SELF ASSESSMENT SYSTEM DAN TEKNOLOGI INFORMASI PERPAJAKAN TERHADAP KEPATUHAN PAJAK MELALUI TAX EVASION (Studi Kasus Pada Wajib Pajak di KPP Pratama Rengat) - NURFITRIANI, NURFITRIANI; RIFAYANI, DESIYANTI; TRIWAHYUNI, NADIA; ALQORNI, NISA; NURAINI, NURAINI (Fakultas Ekonomi Universitas Islam Indragiri, 2023)
This research aims to assess the influence of the self-assessment system and tax information technology on tax compliance through tax evasion. The sample used is taxpayers registered at the Rengat KPP in Prov. Riau as many as 105 respondents. The type of data used is primary data by distributing questionnaires. The data analysis tool used is SEM with the help of PLS Ver. 3. The results of this research show that the direct relationship between the self-assessment system and tax information technology has no effect on tax compliance. However, the self-assessment system and tax information technology have an influence on tax evasion. In an indirect relationship (intervening), the results show that tax evasion mediates the influence of the self-assessment system on tax compliance, while tax evasion cannot mediate the influence of tax information technology on tax compliance